Evaluation of the quality of life among elderly female athletes - Sguizzatto, Guilherme Turolla; Garcez-Leme, Luiz Eugênio; Casimiro, Luciana (São Paulo Medical Journal, 2006)
OBJECTIVE: To analyze quality of life (QOL) in elderly athletes. DESIGN: Transversal, controlled study. METHODS: Female athletes over 60 years who run 15 km, and a control group consisting of 15 healthy, sedentary, women over 60 were studied. Questionnaires on QOL and Depression were applied. RESULTS: Athletes show better functional capacity (98.8 versus 73.3), less pain (90.6 versus 64.9), better general state of health (86.8 versus 66.8) and better vitality (86.2 versus 67.3). Differences were observed in emotional characteristics (89.6 versus 60.0) and mental health (84.3 versus 68.3), with fewer depressive answers (1.9 versus 3.8). CONCLUSION: Regular physical activity was related to better quality of life.